A Case of Invasive Mole (Faridpur Medical College Journal, 2017)
Invasive mole is a condition where a molar pregnancy, such as a partial hydatidiform mole or complete hydatidiform mole, invades the wall of the uterus, potentially spreading and metastasizing to other parts of the body. Here is a case who presented with history of evacuation for molar pregnancy. She presented with irregular P/V bleeding on and off and after admission silent perforation with massive haemoperitoneum was detected for which emergency laparotomy was done. She recovered and was followed up till her b-hCG levels were within normal limits. As patient presented to us with haemoperitoneum and on laparotomy, there was invasion into whole of the uterus, it could not be saved and hysterectomy was done.Faridpur Med. Coll. J. Jul 2017;12(2): 86-87